The Hysteretic Behavior of Partially Pre-Stressed Beam-Column Joint Sub-assemblages Made of Reactive Powder Concrete - Siti Aisyah Nurjannah; Bambang Budiono; Iswandi Imran; Saptahari Sugiri (Journal of Engineering and Technological Sciences, 2016)
Reactive powder concrete (RPC) is an alternative to normal concrete (NC) allowing for significantly higher strength of partially pre-stressed concrete structures. In the Indonesian national standard SNI 03-2847-2013 (2013) and the American standard ACI 318-14 (2014), the partial pre-stressed ratio (PPR) is limited to a maximum of 25.0 percent to ensure that pre-stressed concrete structures remain ductile and capable to dissipate seismic energy sufficiently. The objective of this experimental study was to investigate the hysteretic performance of partially pre-stressed-RPC (PP-RPC) for both interior and exterior beam-column joint sub-assemblages. Four specimens with different levels of PPR were tested with a combination of constant axial compression and cyclic lateral loads. The PPR used for the first and the second two specimens were 22.8% and 33.8%, respectively. The strength of the RPC was 101.60 MPa for all specimens. The results showed that increasing the PPR of PP-RPC improves its hysteretic performance. The best performing specimen, with a PPR of 33.8%, had a ductility that was 1.97 times that of the specimen with a PPR of 22.8%.